USEFUL FORMULAE FOR DDB AND SYD DEPRECIATION. - Myers, John H. (The Accounting Review, 1958)
The article presents some formulae for the calculation of depreciation using declining balance method (DDB) and sum-of-years-digits method. These formulae will enable the non-mathematician accountant to compute such future provisions and reserve balances directly. These formulae may be used for calculating isolated items without the necessity of calculating the intervening items. The auditor can use them to test depreciation provisions computed by his client on a year-by-year basis. The tax planner can use them to see just what depreciation he will have left in later years. Many other similar applications will occur to the reader. In addition to these computational uses the formulae may be used for theoretical computations of behavior in the general case. Since the formulae are applicable in all instances, general rules may be proved. It is commonly stated that shortly after the mid-point of life it is advisable to switch from DDB to straight-line depreciation. To base this statement on observations of a number of specific examples is dangerous.